COMMUNITY EMPOWERMENT THROUGH KSPPS BMT ANDURING PADANG - Maidawati Maidawati (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2022)
This article aims to analyze the role of KSPPS BMT Anduring Padang in empowering the people's economy through the financing it provides to customers. The data used are primary data obtained through interviews with sharia cooperative managers and customers of KSPPS BMT Anduring, as well as through observation and documentation, while secondary data is obtained from articles, books, magazines and other relevant references. The data analysis technique was carried out using analysis of reduction, display, verification and descriptive narration. The results of the study show: First, increasing the productivity of small entrepreneurs (customers), because, with the additional capital provided by KSPPS BMT, customers can develop their business; Second, increasing people's income, because with the financing provided, customers, can continue and develop their business and ultimately increase people's income; Third, to create jobs, the financing provided by KSPPS BMT Anduring is used by customers to start their business, this will cause a lot of workers to be absorbed in carrying out the business, especially workers from the family environment. This proves that the distribution of funds carried out by KSPPS BMT Anduring has played a significant role in empowering the economy of the community (customers) because the implications of the provision of financing provided have achieved the goal of economic empowerment of the people, namely forming a more independent society. However, KSPPS BMT Anduring should be followed by assistance in business management and giving spiritual showers in the form of religious lectures, the aim is to remind customers about Islamic principles in doing business and their obligations in paying debts so that this business can be used as one of the strategies of KSPPS BMT Anduring to minimize problem financing.